Die Epidemiologie der peripheren arteriellen Verschlusskrankheit und deren sozioökonomische Bedeutung – Synopse - Calo, P.; Corvalan, J.; Behrendt, C. -A.; Boeckler, D.; Ruemenapf, G.; Rother, Ulrich; Uhl, C.; Goertz, H. (Gefässchirurgie, 2021)
Peripheral arterial occlusive disease (PAOD) is the manifestation of atherosclerosis as a systemic vascular disease. Worldwide there is an increasing prevalence of up to 10%, which increases with the aging of the population to 20% in patients over 70 years of age. Only 25% of patients with PAOD are symptomatic. Women tend to be diagnosed at an older age than men and are often already at the stage of critical limb ischemia (CLI). In addition to the functional impairments PAOD serves as an important marker for cardiovascular and cerebrovascular morbidity and mortality. For example, the 1‑year mortality for patients with CLI can be as high as 23%. Early diagnosis and evidence-based treatment can slow the course of this disease, improve the quality of life and reduce the rate of major amputations. The costs for inpatient and outpatient treatment of the target population are significant. In Germany it was observed that treatment costs increased by 21% from 2007 to 2009, with inpatient costs representing 4.9% of the total costs. Furthermore, the overall worldwide population over 65 years old is expected to double in the next 35 years. Thus, given recent demographic developments, PAOD represents a considerable medical and financial challenge for the healthcare system.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Demographics; Health care costs; Incidence; Mortality; Prevalence